Release film used for manufacturing membrane-electrode assembly

The release film with a polystyrene resin and a surface free energy of 42.0 mJ/m² addresses the insufficient peelability of conventional films from proton-conducting membranes, enhancing the manufacturing efficiency of membrane electrode assemblies.

JP2025063600AActive Publication Date: 2025-04-16DAICEL CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023172950
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-04
Publication Date
2025-04-16
Estimated Expiration
2043-10-04

AI Technical Summary

Technical Problem

Conventional mold release films exhibit insufficient release properties, particularly in peeling from proton-conducting membranes used in solid polymer fuel cells.

Method used

A release film comprising a substrate layer and a release layer with a polystyrene resin as the main material, having a surface free energy of 42.0 mJ/m², which enhances peelability from ion exchange resin layers.

Benefits of technology

The release film achieves excellent peelability from both electrolyte membranes and catalyst layers, thereby improving the productivity of membrane electrode assemblies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025063600000001_ABST
    Figure 2025063600000001_ABST
Patent Text Reader

Abstract

To provide a release film 2 which is excellent in peelability from an ion exchange resin layer.SOLUTION: A release film 2 has a base material layer 4, and a release layer 6 laminated on the base material layer 4. The main material of the release layer 6 is a polystyrene-based resin. A preferable polystyrene resin is an alkyl-substituted polystyrene resin. A preferable alkyl-substituted polystyrene resin is poly(4-methylstyrene) and poly(4-tert-butylstyrene). Surface free energy of the release layer 6 is 42.0 mJ / m2 or less. An ion exchange resin layer may be formed on the release film 2.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present specification discloses a release film used in a process for producing a membrane electrode assembly, which is a component of a polymer electrolyte fuel cell. The present specification further discloses a method for producing the membrane electrode assembly. [Background technology]

[0002] A solid polymer electrolyte fuel cell has a membrane electrode assembly. The membrane electrode assembly includes a solid polymer electrolyte membrane and two catalyst layers. Each catalyst layer is bonded to a surface of the electrolyte membrane. Both the electrolyte membrane and the catalyst layers are ion exchange resin layers.

[0003] In the manufacture of a membrane electrode assembly, an electrolyte membrane is formed on a first release film, and a catalyst layer is formed on a second release film. The catalyst layer is brought into contact with the electrolyte membrane. The electrolyte membrane and the catalyst layer are heated and pressurized to bond the catalyst layer to the electrolyte membrane. The first release film is then peeled off from the electrolyte membrane. The first release film is required to have appropriate adhesion to the electrolyte membrane and appropriate releasability. The second release film is peeled off from the catalyst layer. The second release film is required to have appropriate adhesion to the catalyst layer and appropriate releasability.

[0004] JP 2014-175116 A discloses a release film having a base layer and a release layer. The material of the release layer is syndiotactic polystyrene. This release film has excellent releasability to an ion exchange resin layer. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP2014-175116A Summary of the Invention [Problem to be solved by the invention]

[0006] Conventional release films have insufficient releasability from ion-exchange resin layers, and there is a demand for improvement in releasability from proton conductive membranes as electrolyte membranes, in particular.

[0007] The applicant's intention is to provide a release film that has excellent releasability to an ion exchange resin layer. [Means for solving the problem]

[0008] The release film disclosed in the present specification can be used in the production of a membrane electrode assembly. This release film has a base layer and a release layer laminated on this base layer. The main material of the release layer is a polystyrene resin. The surface free energy of this release layer is 42.0 mJ / m 2 The following is the result. Effect of the Invention

[0009] This release film has excellent releasability from the electrolyte membrane and from the catalyst layer, and can contribute to the productivity of the membrane electrode assembly. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a cross-sectional view showing a part of a release film according to one embodiment. [Diagram 2] FIG. 2 is a flow chart showing a method for producing a membrane electrode assembly in which the release film of FIG. 1 is used. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Preferred embodiments will be described below with reference to the drawings as appropriate. Each configuration and their combination in each embodiment is an example. Modifications such as omission and substitution of configurations in the embodiments are possible within the scope of the present disclosure, and other configurations can also be added to the embodiments. The scope of disclosure of this specification is not to be interpreted as being limited by the embodiments. Each aspect disclosed in this specification may be combined with any other feature disclosed in this specification.

[0012] [Release film] 1 shows a release film 2. This release film 2 has a base layer 4 and a release layer 6. The release layer 6 is laminated on the base layer 4. The release film 2 may have another layer located between the base layer 4 and the release layer 6. The release film 2 may have another layer located below the base layer 4.

[0013] [Base material layer] A typical material for the base material layer 4 is a thermoplastic resin. As described later, the release film 2 is used in the manufacturing process of a membrane electrode assembly. In this manufacturing process, the release film 2 is heated. Furthermore, tension is applied to this release film 2 in the manufacturing process. The base material layer 4, which is made of a thermoplastic resin that does not stretch easily even when tension is applied in a high-temperature environment, can suppress the stretching of the release film 2. The release film 2 that does not stretch easily can suppress unintended peeling of the electrolyte membrane or catalyst layer, which will be described later, in the manufacturing process of the membrane electrode assembly.

[0014] Examples of thermoplastic resins suitable for the base layer 4 include polypropylene, cyclic polyolefin, polyester, polyamide, polyimide, polycarbonate, polyphenylene ether, polyphenylene sulfide, and cellulose ester. From the viewpoint of excellent heat resistance and flexibility, polyester is particularly preferred. Examples of preferred polyesters include poly C2-4 alkylene arylate resins such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN). Two or more resins may be used in combination in the base layer 4. The material of the base layer 4 may be a thermosetting resin. The material of the base layer 4 may be a composition containing a resin and an additive.

[0015] A preferred base layer 4 from the viewpoint of suppressing elongation of the release film 2 is a stretched film. A uniaxially stretched film and a biaxially stretched film can be used as the base layer 4. From the viewpoint of strength, a biaxially stretched film is preferred. Each of the longitudinal stretching ratio and the transverse stretching ratio in the biaxially stretched film is preferably 1.5 or more, more preferably 2.5 or more, and particularly preferably 3.0 or more.

[0016] In FIG. 1, an arrow T1 indicates the thickness of the base material layer 4. The thickness T1 is preferably 1 μm or more and 300 μm or less. The base material layer 4 having a thickness T1 of 1 μm or more can suppress the elongation of the release film 2 in the manufacturing process of the membrane electrode assembly. From this viewpoint, the thickness T1 is more preferably 10 μm or more, and particularly preferably 20 μm or more. The base material layer 4 having a thickness T1 of 300 μm or less does not inhibit the productivity of the membrane electrode assembly. From this viewpoint, the thickness T1 is more preferably 200 μm or less, and particularly preferably 100 μm or less.

[0017] [Release layer] A typical release layer 6 is a resin film. The surface free energy of this release layer 6 is 42.0 mJ / m 2As described below, in the manufacturing process of the membrane electrode assembly, an electrolyte membrane is formed on the release film 2. The release film 2 is peeled off from this electrolyte membrane. The release film 2 needs to have releasability to the electrolyte membrane. In the manufacturing process of the membrane electrode assembly, a catalyst layer is also formed on the release film 2. The release film 2 is peeled off from this catalyst layer. The release film 2 needs to have releasability to the catalyst layer. The release layer 6 is in direct contact with the electrolyte membrane or the catalyst layer. The surface free energy is 42.0 mJ / m 2 The release layer 6 having a surface free energy of 41.5 mJ / m or less can contribute to the peelability of the electrolyte membrane and the catalyst layer. 2 Less than 41.0 mJ / m is more preferable. 2 The lower limit of the achievable surface free energy is particularly preferably 20 mJ / m 2 It is.

[0018] The contact angles of water, diiodomethane, and bromonaphthalene measured with a contact angle meter are used to calculate the surface free energy γs. The contact angles are measured in an environment with a temperature of 23°C and a humidity of 60% RH. The contact angle is measured 5 seconds after the liquid is dropped. The surface free energy γs is calculated based on the Kitazaki-Hata theory. The formula for the calculation is as follows: γs = γsd + γsp + γsh In this formula, γ represents the dispersion component, γ represents the polar component, and γ represents the hydrogen bond component. An example of a device suitable for the measurement is the fully automatic contact angle meter "DMs-401 (Kyowa Interface Science Co., Ltd.)". Calculations can be performed using the calculation software in the software (FAMAS) of this contact angle meter.

[0019] Various resins capable of achieving the above-mentioned surface free energy can be used as the material of the release layer 6. Preferable resins include polystyrene resin, cyclic polyolefin resin, polypropylene resin, and polymethylpentene resin.

[0020] A resin particularly suitable for the release layer 6 is a polystyrene resin. The polystyrene resin can be obtained by polymerization of an aromatic vinyl monomer. Examples of aromatic vinyl monomers include styrene; alkyl-substituted styrene; alkoxy-substituted styrene such as methoxystyrene and ethoxystyrene; halogen-substituted styrene such as o-chlorostyrene, m-chlorostyrene, p-chlorostyrene, o-bromostyrene and o-fluorostyrene; α-alkyl-substituted styrene; aryl-substituted styrene; and vinylnaphthalene. The polystyrene resin may be obtained from two or more monomers.

[0021] A preferred monomer is alkyl-substituted styrene. In alkyl-substituted styrene, some of the hydrogen atoms on the benzene ring are substituted with alkyl groups. Examples of the alkyl group include methyl, ethyl, propyl, butyl, pentyl, and hexyl groups. Examples of the alkyl-substituted styrene include o-methylstyrene, m-methylstyrene, p-methylstyrene, vinylxylene, p-ethylstyrene, p-isopropylstyrene, butylstyrene, pt-butylstyrene, and 2,4-dimethylstyrene. Polymerization of alkyl-substituted styrene produces an alkyl group-substituted polystyrene resin. This alkyl group-substituted polystyrene resin has a polymerization energy of 42.0 mJ / m 2 This alkyl group-substituted polystyrene resin can contribute to the releasability of the release layer 6 with respect to the ion exchange resin layer.

[0022] Polystyrene resins can also be obtained by copolymerizing alkyl-substituted styrene with other monomers. In this case, the ratio of alkyl-substituted styrene to all monomers is preferably 50 mol% or more, more preferably 70 mol% or more, and particularly preferably 80 mol% or more. Examples of other monomers include α-olefin monomers such as ethylene, propylene, butene, hexene, and octene; acrylic monomers such as (meth)acrylic acid, methyl (meth)acrylate, ethyl (meth)acrylate, cyclohexyl (meth)acrylate, and phenyl (meth)acrylate; cyanide vinyl monomers such as (meth)acrylonitrile; unsaturated polyvalent carboxylic acid monomers and their acid anhydrides such as maleic acid; diene monomers such as butadiene and isoprene; and cyclic diene monomers such as cyclopentadiene and dicyclopentadiene.

[0023] A proton conductive membrane is known as a high-performance electrolyte membrane. This proton conductive membrane has a high sulfonic acid density. This sulfonic acid can inhibit the peelability of the release film 2 from the proton conductive membrane. In the production of a membrane electrode assembly in which the electrolyte membrane is a proton conductive membrane, the requirement for the peelability of the release film 2 is significant. From the viewpoint of peelability from the proton conductive membrane, polystyrene resins particularly suitable for the release layer 6 are poly(4-methylstyrene) and poly(4-tert-butylstyrene).

[0024] Polystyrene resins include a type having an atactic structure (atactic polystyrene resin), a type having an isotactic structure (isotactic polystyrene resin), and a type having a syndiotactic structure (syndiotactic polystyrene resin). From the viewpoint of appropriate adhesion to the ion exchange resin layer, atactic polystyrene resin is preferred. Atactic polystyrene resins can be obtained by radical polymerization of aromatic vinyl monomers. Atactic polystyrene resins are amorphous.

[0025] From the viewpoint of heat resistance of the release layer 6, the weight average molecular weight of the polystyrene resin is preferably 10,000 or more, more preferably 100,000 or more, and particularly preferably 150,000 or more. From the viewpoint of ease of production, the weight average molecular weight is preferably 1,000,000 or less, more preferably 500,000 or less, and particularly preferably 350,000 or less. The weight average molecular weight is measured in terms of polystyrene by gel permeation chromatography.

[0026] The material of the release layer 6 may be a composition containing a polystyrene resin and an additive. The material of the release layer 6 may be a composition containing a polystyrene resin and another resin. The material of the release layer 6 may be a composition containing a polystyrene resin, another resin, and an additive. In either composition, the ratio of the polystyrene resin to the total amount of resin is 50% by mass or more. In other words, the main material of the release layer 6 is a polystyrene resin. The ratio of the polystyrene resin is more preferably 70% by mass or more, and particularly preferably 80% by mass or more. This ratio may be 100% by mass.

[0027] Examples of additives that can be included in the composition of the release layer 6 include fillers, lubricants such as wax, fatty acid esters, and fatty acid amides, antistatic agents, stabilizers such as antioxidants, heat stabilizers, and light stabilizers, flame retardants, viscosity modifiers, thickeners, and defoamers. The composition may include organic or inorganic particles.

[0028] In FIG. 1, an arrow T2 indicates the thickness of the release layer 6. The thickness T2 is preferably 0.1 μm or more and 20 μm or less. A release film 2 in which the thickness T2 of the release layer 6 is 0.1 μm or more has excellent releasability to the ion exchange resin layer. From this viewpoint, the thickness T2 is more preferably 0.3 μm or more, and particularly preferably 0.5 μm or more. A release layer 6 in which the thickness T2 is 20 μm or less does not inhibit the productivity of the membrane electrode assembly. From this viewpoint, the thickness T2 is more preferably 10 μm or less, and particularly preferably 5 μm or less.

[0029] [Thickness ratio] The ratio (T2 / T1) of the thickness T2 of the release layer 6 to the thickness T1 of the base layer 4 is preferably 5 / 1 to 1 / 10, more preferably 3 / 1 to 1 / 5, and particularly preferably 2 / 1 to 1 / 3.

[0030] [Release film manufacturing method] Examples of the method for laminating the release layer 6 onto the base layer 4 include a coating method, a coextrusion method, an extrusion lamination method, a pressure bonding method, and an adhesive method. In terms of smoothness of the release layer 6, the coating method is preferred. In the coating method, a solution or dispersion containing a polystyrene resin is coated onto the base layer 4. Examples of the solvent for the solution or dispersion include aromatic hydrocarbons such as benzene, toluene, and xylene; alicyclic hydrocarbons such as cyclohexane, cyclohexanone, and cyclohexene; halogenated hydrocarbons such as dichloromethane and dichloroethane; cyclic amides such as N-methyl-2-pyrrolidone; and cyclic ethers such as dioxane. Two or more types of solvents may be used in combination.

[0031] Examples of preferred coating methods include a roll coater method, an air knife coater method, a blade coater method, a rod coater method, a reverse coater method, a bar coater method, a comma coater method, a die coater method, a gravure coater method, a screen coater method, a spray method, and a spinner method. From the viewpoint of versatility, the blade coater method and the bar coater method are preferred.

[0032] A coating film is obtained by the coating method. The coating film is dried to obtain the release layer 6. The release layer 6 is in close contact with the base layer 4.

[0033] A release layer 6 may be formed on a surface different from that of the base layer 4 by a coating method or the like. This release layer 6 is laminated on the base layer 4 via an adhesive layer. The adhesive layer may be formed from an adhesive or a pressure-sensitive adhesive. Examples of adhesives include urethane adhesives, acrylic adhesives, polyester adhesives, and polyamide adhesives. Examples of pressure-sensitive adhesives include rubber adhesives, acrylic adhesives, olefin adhesives, and silicone adhesives. The thickness of the adhesive layer is preferably 1 μm or more and 40 μm or less.

[0034] [Method of manufacturing membrane electrode assembly] An example of a method for manufacturing a membrane electrode assembly is shown in Figure 2. This manufacturing method includes forming an electrolyte membrane (STEP 1), forming a front-side catalyst layer (STEP 2), bonding (STEP 3), peeling (STEP 4), forming a back-side catalyst layer (STEP 5), bonding (STEP 6), and peeling (STEP 7).

[0035] In the formation of the electrolyte membrane (STEP 1), first, the resin of the electrolyte membrane is dissolved in a solvent to obtain a first coating liquid. Preferred solvents include water, alcohols such as methanol, ethanol, isopropanol, and 1-butanol, ketones such as acetone and methyl ethyl ketone, ethers such as dioxane and tetrahydrofuran, and sulfoxides such as dimethyl sulfoxide.

[0036] This first coating liquid is coated onto the release layer of the release film 2 (first release film) shown in Figure 1. Preferred coating methods include a roll coater method, an air knife coater method, a blade coater method, a rod coater method, a reverse coater method, a bar coater method, a comma coater method, a die coater method, a gravure coater method, a screen coater method, a spray method, and a spinner method. A coating film is obtained by coating.

[0037] This coating film is heated. The heating temperature is preferably 80°C or higher and 200°C or lower, and particularly preferably 100°C or higher and 150°C or lower. The coating film is dried by heating to obtain an electrolyte membrane. Drying may be performed at room temperature. This electrolyte membrane and the first release film constitute a laminate. In this laminate, the electrolyte membrane is in close contact with the first release film. The back side of the electrolyte membrane is in contact with the first release film. The front side of the electrolyte membrane is exposed.

[0038] In the formation of the front catalyst layer (STEP 2), first, the resin of this catalyst layer is dissolved in a solvent to obtain a second coating liquid. The preferred solvent is the same as that described above for the first coating liquid. This second coating liquid is coated onto the release layer of the second release film. In this embodiment, the specifications of the second release film are the same as those of the first release film. The preferred coating method is the same as that described above for the first coating liquid. A coating film is obtained by coating.

[0039] This coating film is heated. The heating temperature is preferably 50°C or higher and 150°C or lower, particularly preferably 60°C or higher and 120°C or lower. The coating film is dried by heating to obtain a front catalyst layer. Drying may be performed at room temperature. This front catalyst layer is in close contact with the second release film. The front side surface of the front catalyst layer is in contact with the second release film. The rear side surface of the front catalyst layer is exposed.

[0040] In the bonding (STEP 3), the rear side of the front catalyst layer is joined to the front side of the electrolyte membrane. This results in a laminate including the first release film, the electrolyte membrane, the front catalyst layer, and the second release film. This laminate is heated and pressurized. The heating temperature is preferably 80°C or higher and 200°C or lower, more preferably 100°C or higher and 180°C or lower, and particularly preferably 110°C or higher and 150°C or lower. The pressing pressure is preferably 0.1MPa or higher and 20MPa or lower, more preferably 0.5MPa or higher and 15MPa or lower, and particularly preferably 1MPa or higher and 10MPa or lower. The heating and pressing causes the front catalyst layer to firmly adhere to the electrolyte membrane. As described above, each release film 2 has a base layer 4 that is flexible and difficult to stretch. Furthermore, this release film 2 includes a release layer 6 that has a suitable adhesion to the ion exchange resin layer. Therefore, in the heating and pressing process, unintended peeling of the first release film from the electrolyte membrane can be suppressed. Furthermore, unintentional peeling of the second release film from the front catalyst layer can be suppressed.

[0041] In the peeling step (STEP 4), the first release film is peeled off from the electrolyte membrane. The surface free energy of the first release film is 42.0 mJ / m 2 or less. Therefore, the first release film can be easily peeled off from the electrolyte membrane. Even if the electrolyte membrane is a proton conductive membrane, the first release film can be easily peeled off from this proton conductive membrane. Even if the electrolyte membrane has a sulfonic acid equivalent mass of 800 g / mol (SO3H) or less, the first release film can be easily peeled off from this electrolyte membrane. The peeling exposes the back side of the electrolyte membrane.

[0042] In the formation of the backside catalyst layer (STEP 5), the resin of this catalyst layer is first dissolved in a solvent to obtain a third coating liquid. The preferred solvent is the same as that described above for the first coating liquid. This third coating liquid is coated onto the release layer of the third release film. In this embodiment, the specifications of the third release film are the same as those of the first release film. The preferred coating method is the same as that described above for the first coating liquid. A coating film is obtained by coating.

[0043] This coating film is heated. The preferred heating temperature is the same as that described above for the second coating liquid. The coating film is dried by heating to obtain a backside catalyst layer. Drying may be performed at room temperature. This backside catalyst layer is in close contact with the third release film. The backside surface of the backside catalyst layer is in contact with the third release film. The front side of the backside catalyst layer is exposed.

[0044] In the bonding (STEP 6), the front side of the backside catalyst layer is joined to the back side of the electrolyte membrane. This results in a laminate including the third release film, the backside catalyst layer, the electrolyte membrane, the frontside catalyst layer, and the second release film. This laminate is heated and pressurized. The heating temperature is preferably 80°C or higher and 200°C or lower, more preferably 100°C or higher and 180°C or lower, and particularly preferably 110°C or higher and 150°C or lower. The pressing pressure is preferably 0.1MPa or higher and 20MPa or lower, more preferably 0.5MPa or higher and 15MPa or lower, and particularly preferably 1MPa or higher and 10MPa or lower. The heating and pressing causes the backside catalyst layer to firmly adhere to the electrolyte membrane. As described above, each release film 2 has a base layer 4 that is flexible and difficult to stretch. Furthermore, this release film 2 includes a release layer 6 that has a suitable adhesion to the ion exchange resin layer. Therefore, in the heating and pressing process, unintended peeling of the second release film from the frontside catalyst layer can be suppressed. Furthermore, unintentional peeling of the third release film from the backside catalyst layer can be suppressed.

[0045] In the peeling step (STEP 7), the second release film is peeled off from the front catalyst layer, and the third release film is peeled off from the back catalyst layer. The surface free energy of each release film 2 is 42.0 mJ / m 2 The films can be easily peeled off from the catalyst layers. By peeling, a laminate consisting of the back catalyst layer, the electrolyte membrane, and the front catalyst layer is obtained. A gas supply layer and the like are further laminated on this laminate to obtain a membrane electrode assembly.

[0046] The specifications of the second release film may be different from the specifications of the first release film.The specifications of the third release film may be different from the specifications of the first release film. EXAMPLES

[0047] The effects of the examples will be explained below, but the scope of the present specification should not be construed as being limited based on the description of these examples.

[0048] [Example 1] A coating liquid was obtained by dissolving 10% by mass of poly(4-methylstyrene) (Sigma-Aldrich) in 90% by mass of toluene. On the other hand, a polyester film with an easy-adhesion layer ("Cosmoshine (registered trademark) A4100", Toyobo Co., Ltd.) was prepared as a substrate layer. The thickness of this polyester film was 50 μm. The coating liquid was applied to the surface of the easy-adhesion layer of this polyester film with a wire bar #5 to obtain a coating film. This coating film was kept at a temperature of 100° C. for 1 minute and dried to obtain the release film of Example 1.

[0049] [Example 2] A release film of Example 2 was obtained in the same manner as in Example 1, except that a coating liquid was obtained by dissolving 10 mass % of poly(4-tert-butylstyrene) (Sigma-Aldrich) in 90 mass % toluene.

[0050] [Comparative Example 1] A release film of Comparative Example 1 was obtained in the same manner as in Example 1, except that a coating liquid was obtained by dissolving 10 mass % of a cyclic olefin resin ("TOPAS-6015", Polyplastics Co., Ltd.) in 90 mass % toluene.

[0051] [Comparative Example 2] A release film of Comparative Example 2 was obtained in the same manner as in Example 1, except that a coating liquid was obtained by dissolving 10 mass % of a cyclic olefin resin ("ZEONEX480R", Zeon Corporation) in 90 mass % toluene.

[0052] [Comparative Example 3] The release film of Comparative Example 3 was obtained in the same manner as in Example 1, except that 10% by mass of a polyarylate resin ("UNIFINER M-2040", Unitika Ltd.) was dissolved in a mixture of 70% by mass of toluene and 20% by mass of methyl ethyl ketone to obtain a coating liquid.

[0053] [Comparative Example 4] A release film of Comparative Example 4 was obtained in the same manner as in Example 1, except that a coating liquid was obtained by dissolving 10 mass % of polystyrene resin ("G200C", Toyo Styrene Co., Ltd.) in 90 mass % toluene.

[0054] [Comparative Example 5] A commercially available resin film ("HN-200", Kurabo Industries, Ltd.) was prepared as the release film of Comparative Example 5. The material of this resin film was syndiotactic polystyrene. The thickness of this resin film was 35 μm.

[0055] [Comparative Example 6] A commercially available resin film ("Opulent X-88B", Mitsui Chemicals, Inc.) was prepared as the release film of Comparative Example 6. The material of this resin film was polymethylpentene. The thickness of this resin film was 25 μm.

[0056] [Comparative Example 7] 18 parts by mass of dry lamination adhesive ("TM-570V", Toyo Morton Co., Ltd.) and 1 part by mass of curing agent ("CAT-RT37", Toyo Morton Co., Ltd.) were dissolved in an appropriate amount of ethyl acetate to obtain an adhesive with a solid content of 35% by mass. This adhesive was applied to a polyester film with an easy-adhesion layer (the above-mentioned "Cosmoshine (registered trademark) A4100") with a Mayer bar to obtain a coating film. This coating film was kept at a temperature of 80°C for 30 seconds to obtain an adhesive layer. The density of this adhesive layer was 20 g / m2. The thickness of this adhesive layer was 2 μm. Meanwhile, a biaxially oriented polypropylene film ("Trefan (registered trademark) 2500", Toray Industries, Inc.) was prepared. The thickness of this biaxially oriented polypropylene film was 40 μm. This biaxially oriented polypropylene film was layered on the adhesive layer and bonded by a dry lamination method to obtain a release film of Comparative Example 7.

[0057] [Evaluation of peelability-1] An ion exchange resin solution ("Nafion (registered trademark) DS2020CS", DuPont) was prepared as the coating liquid. The equivalent mass of this ion exchange resin solution was 1100±20 g / mol (SO3H), and the solid content was 21% by mass±1% by mass. The coating liquid was applied onto a release film using a Mayer bar to obtain a coating film. This coating film was held at a temperature of 100°C for 3 minutes and dried. This coating film was further subjected to a heat treatment at a temperature of 160°C for 30 minutes to obtain an ion exchange layer. The ion exchange layer was peeled off from the release film using an autograph ("AGS-X", Shimadzu Corporation), and the peeling force was measured. The conditions were as follows. Test piece width: 25mm Angle: 180° Speed: 600mm / min The resulting peel strength was rated according to the following scale: A: The peel strength is less than 100 mN / 25 mm. B: Peel strength is 100 mN / 25 mm or more. The results are shown in Tables 1 and 2 below.

[0058] [Evaluation of peelability-2] A coating solution was obtained by mixing 4 parts by mass of an ion exchange resin solution ("Aquivion (registered trademark) D72-25BS", Sigma Aldrich) and 1 part by mass of 2-propanol. The equivalent mass of this ion exchange resin solution was 720±20 g / mol (SO3H), and the solid content was 25% by mass±1% by mass. The coating solution was applied onto a release film using a Mayer bar to obtain a coating film. This coating film was kept at a temperature of 100°C for 3 minutes and dried. This coating film was further subjected to a heat treatment at a temperature of 160°C for 30 minutes to obtain an ion exchange layer. The ion exchange layer was peeled off from the release film using an autograph ("AGS-X", Shimadzu Corporation), and the peeling force was measured. The conditions were as follows. Test piece width: 25mm Angle: 180° Speed: 600mm / min The resulting peel strength was rated according to the following scale: A: The peel strength is less than 100 mN / 25 mm. B: Peel strength is 100 mN / 25 mm or more. The results are shown in Tables 1 and 2 below.

[0059] [Curl Height] A test piece was cut out from the release film. The size of this test piece was 200 mm x 200 mm. A metal plate with a flat surface was placed in a dryer at a temperature of 120°C, and the test piece was placed on the metal plate. After 5 minutes, the test piece together with the metal plate was removed from the dryer and cooled to room temperature. The maximum amount of lift of the four sides of the test piece from the metal surface was measured. The obtained values ​​were ranked according to the following criteria. A: The maximum value is less than 1.0 cm. B: The maximum value is 1.0 cm or more. The results are shown in Tables 1 and 2 below.

[0060] [Table 1]

[0061] [Table 2]

[0062] As is clear from Tables 1 and 2, the release films of the examples are excellent in various performances. From these evaluation results, the superiority of this release film is clear.

[0063] [Disclosure items] Each of the following sections discloses a preferred embodiment.

[0064] [Item 1] The adhesive sheet includes a base layer and a release layer laminated on the base layer, The main material of the release layer is a polystyrene resin, The surface free energy of the release layer is 42.0 mJ / m 2 A release film for use in the manufacture of a membrane electrode assembly, comprising:

[0065] [Item 2] 2. The release film according to item 1, wherein the main material of the release layer is an alkyl group-substituted polystyrene resin.

[0066] [Item 3] 3. The release film according to item 2, wherein the main material of the release layer is a 4-alkyl group-substituted polystyrene resin.

[0067] [Item 4] 4. The release film according to item 3, wherein the main material of the release layer is poly(4-methylstyrene) or poly(4-tert-butylstyrene).

[0068] [Item 5] 5. The release film according to any one of items 1 to 4, wherein the main material of the release layer is atactic polystyrene.

[0069] [Item 6] (1) A substrate layer and a release layer laminated on the substrate layer, the release layer being mainly made of a polystyrene resin and having a surface free energy of 42.0 mJ / m 2 A step of forming an electrolyte membrane on a surface of a first release film, (2) forming a catalyst layer on the surface of a second release film; (3) bonding the catalyst layer to the electrolyte membrane; and (4) peeling off the first release film from the electrolyte membrane The method for producing a membrane electrode assembly comprising the steps of:

[0070] [Item 7] 7. The method according to claim 6, wherein in the step (1), a proton conductive membrane is formed as the electrolyte membrane.

[0071] [Item 8] A laminate including a release film and an electrolyte membrane laminated on the release film, The release film has a base layer and a release layer laminated on the base layer, the main material of the release layer is a polystyrene resin, and the surface free energy of the release layer is 42.0 mJ / m 2 is as follows: The electrolyte membrane has a sulfonic acid equivalent mass of 800 g / mol (SO3H) or less. [Industrial Applicability]

[0072] The release film described above is suitable for producing various molded articles made of ion exchange resins. [Explanation of symbols]

[0073] 2. Release film 4...Base material layer 6...Release layer

Claims

1. The adhesive sheet includes a base layer and a release layer laminated on the base layer, The main material of the release layer is a polystyrene resin, The surface free energy of the release layer is 42.0 mJ / m 2 A release film for use in the manufacture of a membrane electrode assembly, comprising:

2. The release film according to claim 1 , wherein the main material of the release layer is an alkyl group-substituted polystyrene resin.

3. The release film according to claim 2 , wherein the main material of the release layer is a 4-alkyl group-substituted polystyrene resin.

4. The release film according to claim 3, wherein the main material of the release layer is poly(4-methylstyrene) or poly(4-tert-butylstyrene).

5. The release film according to claim 1 or 2, wherein the main material of the release layer is atactic polystyrene.

6. (1) A substrate layer and a release layer laminated on the substrate layer, the release layer being mainly made of a polystyrene resin, and the surface free energy of the release layer being 42.0 mJ / m 2 A step of forming an electrolyte membrane on a surface of a first release film, (2) forming a catalyst layer on the surface of a second release film; (3) bonding the catalyst layer to the electrolyte membrane; and (4) A step of peeling off the first release film from the electrolyte membrane. The method for producing a membrane electrode assembly comprising the steps of:

7. The method according to claim 6, wherein in the step (1), a proton conductive membrane is formed as the electrolyte membrane.

8. A laminate including a release film and an electrolyte membrane laminated on the release film, The release film has a base layer and a release layer laminated on the base layer, the main material of the release layer is a polystyrene resin, and the surface free energy of the release layer is 42.0 mJ / m 2 is as follows: The sulfonic acid equivalent mass of the electrolyte membrane is 800 g / mol (SO 3 H) A laminate,

Citation Information

Patent Citations

  • Laminated film

    JP2011161749A

  • Laminate for fuel battery fabrication, manufacturing method thereof, and manufacturing method of fuel battery

    JP2014175116A

  • Release film for use in the manufacture of electrolyte membranes or membrane electrode assemblies

    JP2022540472A

  • Release film

    WO2014045888A1

  • Mold release film and method for producing flexible printed circuit board

    WO2018173683A1